A Method for the Construction of a New Reallocation Plan in Land Consolidation and its Application - Ayranci, Yasar (2009)
A number of factors in relation to land classification, farmers' preference, fixed installations and distance have to be considered in the reallocation process of land consolidation. These factors vary from one country to other, but the most feasible solutions are those that work in harmony with the current conditions in a specific country. In this research, a mathematical optimization model is presented, which is suitable for the construction of a new reallocation plan in land consolidation. The model encompasses the factors of "distance", "soil index", "farmer preference" and "fixed installation" within its optimization process. The results showed that it will be usable in land consolidation and will generally be acceptable to farmers.
Keywords: Land management